2008
DOI: 10.1111/j.1440-1819.2008.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and its association with self‐esteem, family, peer and school factors in a population of 9586 adolescents in southern Taiwan

Abstract: Aims:The aim of the present study was to gain insight into the prevalence of depression and its association with self-esteem, family, peer and school factors in a large-scale representative Taiwanese adolescent population.Methods: A total of 12 210 adolescent students were recruited into the present study. Subjects with a score >28 on the Center for Epidemiological Studies' Depression Scale were defined as having significant depression; the Rosenberg Self-Esteem Scale, Adolescent Family and Social Life Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
98
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 63 publications
22
98
4
1
Order By: Relevance
“…This may be because older students feel that they are approaching real life struggles of employment, marriage, and other financial problems. These results are consistent with other studies carried out among university students which concluded that older students have higher prevalence of depression symptoms [34,44,45], although some other studies have failed to find this association [2,36,40,46].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may be because older students feel that they are approaching real life struggles of employment, marriage, and other financial problems. These results are consistent with other studies carried out among university students which concluded that older students have higher prevalence of depression symptoms [34,44,45], although some other studies have failed to find this association [2,36,40,46].…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has shown that several socio-demographic factors increase the risk for depression in college students; namely, age, sex, residence, family income, parental education, and parental occupation [14,34,36,40,45]. In this study, it was found that rates of depression were higher among lower class students than higher class ones regardless of the SES domains used.…”
Section: Discussionmentioning
confidence: 50%
“…In addition this study showed a significant relationship between family history of depression and depression as those with positive family history of depression are 6.6 times more likely to have depression and this is in agreement with Daryanavard et al [13,36]. Family environment is a very strong place that can affect the development and wellbeing of adolescent.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have also linked polygamous family settings to adolescent depression [25] [26]. This might be due to parents in polygamous family settings being unable to fulfil the needs of their growing children as a result of more numbers in the family.…”
Section: Discussionmentioning
confidence: 99%